Strategi Komunikasi Amphuri dalam Membangun Citra Perusahaan pada Anggota - Rima Rachmaningsih; Halomoan Harahap (CV. Syntax Corporation Indonesia, 2022)
Amphuri is an organization consisting of PIHK (Special Hajj Organizer) and PPIU (Umrah Organizing Company) in Indonesia is democratic, free, independent and responsible in handling the world of hajj and Umrah in the broadest sense and creating a conducive and competitive climate. The hope of this association is to have strong bargaining power in negotiating with Muassasah and various other stakeholders. One of the organizational communication strategies implemented by AMPHURI in building the company's image to members is to be a media liaison between members with the Government of the Republic of Indonesia, the Kingdom of Saudi Arabia and Stakeholders in Indonesia and Saudi Arabia. According to Peter R. Monge and Noshir S, Network Theory is